(untitled) (Research, Society and Development, 2023)
The service life of pavements has mostly been shorter than expected, due to several factors, such as geometric and loading. Thus, the dimensioning method of a pavement must consider for the distribution of stresses and strains that it is composed of different layers and materials, with their respective stiffnesses and thicknesses. Thus, this study aims to analyze the impact that pavement structures designed by the empirical and empirical-mechanistic methods provide on the cracked area and the design period of flexible pavements. For the design of the pavements, the traffic information of a road section of BR-040 and a 10-year design period were considered. And the characteristics of the materials used in the coating layers, base, sub-base and subgrade, were obtained from the analysis of scientific and academic papers. The pavement designed using the empirical-mechanistic method met the requirements for the proposed period, unlike the results obtained for the two pavements dimensioned by the empirical method, which presented a structure that would meet only 50% and 75% of the design life. It was concluded that the pavement structure dimensioned by the empirical-mechanistic method, different from those dimensioned by the empirical method, presented a structure that meets the cracked area criterion in the pavement for the period in which it was designed.